Identification of higher education administration applications efforts to improve digital-based academic services - Dacholfany, Muhammad Ihsan; Noor, Triana Rosalina; Diana, Eka; Nurzen. S, M.; Prayoga, Diansanto (Linguistics and Culture Review, 2021)
The authors believe that the presence of technology, especially digital applications, has not only made it easier for the work of a limited group such as business and banking and other businesses, but this digital application has also provided extraordinary convenience to educational administration matters especially universities. We have collected evidence of researchers’ findings in technology effectiveness in administrative services at universities. Furthermore, this information requires a comprehensive study to summarize the data as a discussion material to identify how the ease of providing high-quality applications can be improved with digital technology application services. In this field, we use a coding application form for a comprehensive data evaluation and conclude that the data findings are significant in answering the problem on the principle of high validity. Based on this, we can understand that technology has revolutionized administrative services at universities, including managing student literacy both from study entry and graduation, it is also helpful for academic services, financial affairs, academic development management. We believe this data is in answering problems and the existence of these findings is an essential input for efforts to develop the application studies using applications to improve the quality of high change services in the future.